What I didn't learn in business school : how strategy works in the real world - Barney, Jay B.; Clifford, Trish Gorman (Boston : Harvard Business Review Press, 2010)
This is a business novel,the story reveals both the strength and limitations of common strategy tools. it demonstrates the tactics for navigating the messy organisational dynamics that can make or break acompany's effort to craft successful strategies.
Includes bibliographical references (p. 213-231).
uaj 07/06/13
Loans
Keywords: Strategic planning; Decision making; Problem solving